DECOMPOSITION OF INDUSTRIAL ENERGY CONSUMPTION IN INDIAN MANUFACTURING: THE ENERGY INTENSITY APPROACH - SAHU, Santosh Kumar; NARAYANAN, K. (Journal of Environmental Management and Tourism; Vol 1 No 1 (2010): JEMT Volume I Issue 1(1) Summer 2010, 2010)
Increasing energy consumption has been one of the major issues in the environmental and industrial economics in the context of global climate change. Recent literature has dealt with several methodological and application issues related to the technique of decomposing changes in industrial energy consumption. In this paper, we examine these issues in the context of another commonly adopted approach to decomposition of aggregate changes in energy intensity of Indian manufacturing industries. The industrial sector accounts for about 37 percent of the total final energy consumption in India. Of this the manufacturing sector consumes about 66 percent (2004-05). The manufacturing sector is one of the energy intensive industries among other industries in India. The scope of the study includes an empirical analysis of General Parametric Divisia Method. This paper follows the energy intensity approach rather the energy consumption approach. This method involves decomposition of the aggregate energy intensity index measured in terms of energy consumption per unit of output. The analysis also includes a comparison of the time series analysis versus the period-wise decomposition. The factors considered are changes in production structure and sectoral energy intensities. The results of the analysis confirm that the changes in sectoral energy intensity play a greater role in the variation in the total energy intensity of Indian Manufacturing compared to the changes in the production structure of the Industries.